Pembuatan komposit dari serat tandan kosong kelapa sawit dengan matrik polipropilen serta penambahan grafting agent PP-g-MA - Elvi Kustiyah; Indrako Wicaksono; Laras Andria Wardani; Sophia Shanti Meilani; Haudi Hasaya (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Indonesia is one of the largest producers of palm oil in the world, and possibly one of the largest generators of empty palm bunch wastes. Researchers have studied these wastes to be utilized as a fuel alternative, additives to concrete, fertilizers, and other uses. However, the amount of empty palm bunch wastes seemed to stay in a high number. Another use of empty bunch conducted in this research was as fillers on polymer composites due to its high content of cellulose The aim of this research is to obtain a new source of material based on natural palm oil waste as a substitute natural minerals that is limited at nature.The methode used was incorporating empty bunch with hot melt mixing, using two roll mills and adding pp-g-ma as a compatibilizer agent. After composites were formed, characterizations were conducted by analyzing micro-structures using Scanning Electron Microscope (SEM) and testing the mechanical properties with tensile strength and elongation. Results of this study showed that the sizes of fibers of the palm bunch greatly affected the results of characterizations. Effects were also shown with effectivity of compatibilizer concentrations and mixing methods